Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 2 - Real Numbers - 2.4 - Exponents - Problem Set 2.4 - Page 76: 99



Work Step by Step

Substituting $x=-8$ into the expression $-x^{2}$, we obtain: $-x^{2}=-(-8)^{2}=-(-8\times-8)=-(64)=-64$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.